2017
DOI: 10.4172/neuropsychiatry.1000303
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Cultivation and Diurnal Cortisol Profiles in Healthy Chinese Elders

Abstract: Objective:Psychobiological research on aging in humans is confounded by individual differences that remain to be characterized more precisely. The present study was designed to address this issue by examining the impact of Network Cultivation, a behavioral tendency to strengthen one's social ties on diurnal cortisol profiles in healthy Chinese elders in Hong Kong. Methods:Authors performed secondary analysis of data reported by Lai [1] using multilevel modelling. Seventy-eight healthy seniors provided saliva s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The CAR can be considered to indicate the effectiveness of cortisol activation, whereas the DS can be regarded as the effectiveness of deactivation: the decline of cortisol from waking to late evening. A stronger CAR and a steeper DS (Lai et al, 2012), and a lower diurnal level (Lai et al, 2017) have been observed in better adjusted Chinese seniors by the first author and associates in separate studies. suggested that this pattern could be a central neuroendocrine feature of better health in elders.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The CAR can be considered to indicate the effectiveness of cortisol activation, whereas the DS can be regarded as the effectiveness of deactivation: the decline of cortisol from waking to late evening. A stronger CAR and a steeper DS (Lai et al, 2012), and a lower diurnal level (Lai et al, 2017) have been observed in better adjusted Chinese seniors by the first author and associates in separate studies. suggested that this pattern could be a central neuroendocrine feature of better health in elders.…”
Section: Introductionmentioning
confidence: 65%
“…An accentuated AUC G has been observed in many pathological conditions such as chronic burnout (Melamed et al, 1999), depression (Belanoff et al, 2002), and chronic stress (Bauer et al, 2000). In healthy populations, a lower AUC G is associated with lower loneliness in college students (e.g., Lai et al, 2019) and better adjustment (Chin et al, 2017;Lai et al, 2017). A recent study in healthy participants has demonstrated that a lower AUC G is associated with a lower risk of experimentally induced upper respiratory infection (Janicki-Deverts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a controlled study of the diurnal rhythm of salivary cortisol among healthy older adults, participants who have previously spent more time and effort in network cultivation tended to exhibit cortisol profiles with a greater CAR (cortisol awakening response) and a more pronounced diurnal decline than their counterparts who have spent less time and effort (Lai et al, 2012). This diurnal profile is stronger among healthy elders (Lai et al, 2017) and, interestingly, more like that exhibited in younger people, implying that cultivation of social ties may serve to ‘rejuvenate’ the diurnal cortisol profile in older adults and hence physiologically prepare them to adapt to social stress (Lai & Lee, 2019).…”
Section: Positive Ageingmentioning
confidence: 99%